An unusual presentation of IgG4-related disease - Upreti Rohit; Hegde Arun; Sengupta Prashant; Gupta Vikas; Jain Anurag; Kovilapu Uday Bhanu (Indian Journal of Rheumatology)
IgG4-related disease (IgG4-RD) is an emerging disease concept that was first recognized in the 21st century. It has since then been attracting substantial attention in many fields of medicine as it tends to involve either synchronously or metachronously, various organs, including the pancreas, bile duct, lacrimal gland, salivary gland, and many others. This umbrella diagnosis now successfully explains a substantial number of disorders, which were previously regarded as “idiopathic.” Reports of the manifestations of IgG4-RD in the head and neck are extremely rare. Otologic manifestations have been reported, but only a handful of cases are available in literature that have been confirmed by immunohistopathology. We, herein, present a case of IgG4-RD of the middle ear, which manifested as a growth in the left mastoid and middle ear cavity, and became symptomatic with symptoms of chronic otitis media in the left ear, and was subsequently diagnosed to have IgG4-RD.